2005
DOI: 10.1113/jphysiol.2005.092155
|View full text |Cite
|
Sign up to set email alerts
|

Dissociated effects of diazepam and lorazepam on short‐latency afferent inhibition

Abstract: Peripheral nerve inputs have an inhibitory effect on motor cortex excitability at short intervals (short-latency afferent inhibition, SAI). This can be tested by coupling electrical stimulation of peripheral nerve with transcranial magnetic stimulation (TMS) of the motor cortex. SAI is reduced by the anticholinergic drug scopolamine, and in patients with Alzheimer's disease. Therefore, it is possible that SAI is a marker of central cholinergic activity important for memory function. The benzodiazepine lorazepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(116 citation statements)
references
References 30 publications
(57 reference statements)
3
110
2
1
Order By: Relevance
“…Indeed, alterations of SAI have been observed in association with cognitive deficits [46][47][48], movement preparation [49], modifications of cholinergic [48], GABAergic [50] and dopaminergic activity [51]. This may also account for the weak, although significant, correlation that we here report between SAI and PDGF-CSF.…”
Section: Discussioncontrasting
confidence: 49%
“…Indeed, alterations of SAI have been observed in association with cognitive deficits [46][47][48], movement preparation [49], modifications of cholinergic [48], GABAergic [50] and dopaminergic activity [51]. This may also account for the weak, although significant, correlation that we here report between SAI and PDGF-CSF.…”
Section: Discussioncontrasting
confidence: 49%
“…This is consistent with the different effects of benzodiazepines on SICI and SAI. SICI is increased by both lorazepam and diazepam but SAI is only slightly increased by diazepam and is reduced by lorazepam (Di Lazzaro et al 2005). Therefore the cortical circuits activated by SAI and SICI are likely to be different.…”
Section: Pa and Ap Directed Current Activate Different Late I-wavesmentioning
confidence: 93%
“…Previous studies investigating SAI in PA current direction also reported that SAI inhibits late I-waves (Di Lazzaro et al 2005;Sailer et al 2003;Tokimura et al 2000), suggesting that the cortical circuits mediating late Iwaves are more susceptible to cortical inhibition than those mediating early I-waves. Consistent with these previous studies, we found that sensory afferent input inhibited the output from M1 at the ISIs around 20 ms not only for PA but also for AP current direction.…”
Section: Pa and Ap Directed Current Activate Different Late I-wavesmentioning
confidence: 99%
“…Cholinergic and GABAergic systems appear to mediate and/or modulate SAI. Scopolamine, an anti cholinergic drug, reduces SAI [58,59] while diazepam, a GABA A modulator, increases SAI [60]. LAI however, is thought to proceed through only a GABAergic system.…”
Section: Short Interval Intra Cortical Inhibition (Sici)mentioning
confidence: 99%